Suplementação oral de 1,25 – Dihidroxicolecalciferol glicosídeo sobre o metabolismo de minerais, serotonina e dopamina em bovinos - Souza, Douglas Machado de (2024)
The plant extract 1,25(OH)2D3 glycoside is the bioactive metabolite of vitamin D and plays an important role in the regulation of blood minerals. However, the effects of continuous oral supplementation on the neurotransmitters serotonin and dopamine and safe doses are not well understood. The study aimed to evaluate the effect of different doses of 1,25(OH)2D3 glycoside on the metabolism of calcium, phosphorus, magnesium, neurotransmitters and its toxic effect in steers. Six Holstein steers, aged between 18 and 24 months with an average initial weight of 472.5 ± 61.5 kg were used in a replicated 3 x 3 Latin square design. Each period lasted 28 days, with 5 days of 1,25(OH)2D3 glycoside administration and 23 days for metabolic cleansing. 1,25(OH)2D3 glycoside was administered individually at doses equivalent to 0, 0.2 and 0.4 µg/kg of body weight (BW) incorporated into a protein-mineral supplement in mash form. Steers were kept in a pasture area with Urochloa brizantha cv. Xaraés. Blood samples were collected before the supply of treatments (-120 h) and 0, 3, 6, 12, 24, 48, 72, 96 and 168 hours after the last dose on the 5th day. Additionally, urine samples were collected 6 and 12 hours after the last treatment supply. Steer behavior was evaluated on the 5th day for 12 hours. Serum calcium and phosphorus increased (P > 0.05) with the inclusion of 1,25(OH)2D3 glycoside. Doses of 0.2 and 0.4 µg/kg showed an increase (P < 0.001) of 8.4% and 12.7% in calcium, respectively, compared to the control group, with peaks in serum concentration found between 24 and 48 h after treatment interruption. Phosphorus increased (P < 0.001) by 21.9% at the dose of 0.2 µg/kg (BW) and by 32.4% at 0.4 µg/kg (BW). After treatment interruption at the dose of 0.4 µg/kg (BW), serum calcium levels returned to baseline values after 4 days and phosphorus levels after 7 days. Serum magnesium showed an increasing trend (P = 0.051). Alkaline phosphatase, serotonin, dopamine and parathyroid hormone did not change. Urinary calcium showed an increasing trend (P = 0.070). The steers did not show clinical signs of intoxication. It was concluded that oral supplementation of 1,25(OH)2D3 glycoside increases serum levels of calcium and phosphorus at doses of 0.2 and 0.4 µg/kg BW without causing clinical signs of intoxication. However, doses higher than 0.2 µg/kg showed persistent effects on elevation of serum calcium and phosphorus.